2011
DOI: 10.1017/s1368980011000346
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status is strongly correlated with grip strength and depression in community-living elderly Japanese

Abstract: Objectives: To evaluate the utility of the Mini-Nutritional Assessment (MNA) in assessing nutritional, physical and psychosocial functions in community-living elderly individuals. Design: A cross-sectional study of elderly individuals investigated in August 2007 and August-September 2008. Nutritional status was assessed using serum biomarkers, anthropometric measurements and the MNA. Physical function was assessed by measuring grip strength and both usual and maximum walking speeds. The Geriatric Depression Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 19 publications
5
29
0
2
Order By: Relevance
“…Yet depressive symptoms can have significant effects. Depressed elders left without proper treatment may experience serious consequences, including increased disability, malnutrition, institutionalization, and even mortality 10,6671. In addition, depressed elders tend to underestimate their functional capacities,72,73 leading to activity restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Yet depressive symptoms can have significant effects. Depressed elders left without proper treatment may experience serious consequences, including increased disability, malnutrition, institutionalization, and even mortality 10,6671. In addition, depressed elders tend to underestimate their functional capacities,72,73 leading to activity restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al (2014) found the same association in Taiwanese older adults. In addition, gait speed and handgrip strength which correlate to physical performance and muscle strength, respectively, have also been associated with depressive symptoms (Atkinson et al, 2007; Kaburagi et al, 2011). However, these studies have used scales that include somatic symptoms such as fatigue for screening of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, weight loss and loss of appetite are the main factors that mediate the relationship between depression and nutritional status (Rubenstein, Harker, Salva`, Guigoz, & Vellas, 2001). Recently, multiple studies have indicated an association between depression and nutritional status in various settings such as outpatient clinics and institutions and in the community (Cabrera, Mesas, Garcia, & de Andrade, 2007;Kaburagi et al, 2011;Smoliner et al, 2009;Wilson, Vaswani, Liu, Morley, & Miller, 1998). In these settings, depression is an independent predictor of nutritional health and a major cause of weight loss (Chen, Chang, Chyun, & McCorkle, 2005;Morley & Kraenzle, 1994;Thompson & Morris, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Email: yoshimura.kazuya.76w@st.kyoto-u.ac.jp relationship among the various variables associated with depression. For example, the young-old (age 65-74 years) and old-old (age 75 years and above) have different predispositions regarding various aspects of both depression and nutritional status (Kaburagi et al, 2011;Kondo, Kazama, Suzuki, & Yamagata, 2008). Older elderly are more likely to experience frailty, physical illness, bereavement and loneliness, which are risk factors contributing to depression (Blazer, 2002;Bruce, 2002).…”
Section: Introductionmentioning
confidence: 99%